Assessing the Reliability, Dimensions, and Variance of Young's Internet Addiction Test by Applying it to Adolescents at the National Psychiatric Hospital in Costa Rica. - Martín Herrero, José A.; Fernández Mora, Karla; Molina Fernández, Antonio (Actas Espanolas de Psiquiatria, 2024)
Background: The Internet Addiction Test (IAT) was the first instrument created specifically to assess Internet addiction (IA). Although it was not validated during its creation, its validity has since been confirmed thanks to subsequent studies. The IAT is the first global psychometric measure tested worldwide that has been used in several studies as a research tool. Regarding the dimensions of the IAT, they were not reported by the creator of the test, during the performed factor analysis. Nonetheless, different studies have defined the test as being one-dimensional and others as having three, four, five, and six dimensions. Methods: In the present study, seven dimensions were identified; however, there is still a lack of consensus about the number of dimensions that accurately define this test. Results: Hence, Young's Internet Addiction Test presents a shortcoming that may be explained by the influence of several factors such as how it was applied, the place where it was applied, and the population to which it was applied. All of these are factors that could be linked to the sociocultural aspects of the adaptations that have been made to the test. Conclusions: Moreover, the first dimension of the IAT found, the loss of self-control, is extremely important because it explains 34% of the variance of the data. However, 74% of the variance is explained by applying the 7 dimensions identified in this research. Also, the reliability analysis showed that the IAT is 89% reliable, which indicates that the elements comprising the test used in this research are suitable for measuring the construct of Internet addiction.